Design and Development of Passive Shock Recovery Systems - Stephenson, John-Joseph (Cranfield University, 2023)
Systems for the recovery of spalled and non-spalled samples have been used for several years. These tend to involve the sample and a series of interior spall plates at the rear of the target through which the shock wave can propagate and reflect. The geometry of these plates is intended to be such that the tension will not occur in the sample, thus preventing spall. The assembly of recovery targets requires great precision, and the construction of a single target can take close to 100-man hours. This work looks at developing a passive recovery system with external spall plate attached to the target momentum ring using epoxy resin. This would significantly reduce the number of man hours required to produce a target, reducing the cost of recovery shots and allowing for more recovery shots to be performed within an experimental run. Recovery-type compression only shots can play a role in the recompaction of spalled metals as the spall plates will keep the sample in compression, allowing the spall plane to recompress while the dynamic work from the shock wave seals up the voids. This work will also look at the use of a ‘passive’ recovery system as part of a 2-stage 'spall and recompaction' test. Should this be verified, this would reduce the cost and complexity of recompaction shots by removing the need for heat bed such as in Jones et al, or multi-stage impactors seen in Hawkins et al.
Keywords: Shock waves; Spall; Recovery; DSDS22 Poster; DSDS22